CATEGORIES, STRUCTURE, AND FUNCTION OF FOLKLORE IN LIMA PULUH DISTRICT COMMUNITIES - Revika Revika; Yenni Hayati (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to determine the categories, structure, and functions of folklore in the MuaroPaitiNagari community. The method used in this research is descriptive method. The results showed that of the 12 folklore found in the Nagari community of MuaroPaiti, there are myths, myths, and fairy tales. The structure of folklore in the village of MuaroPaiti includes plot/plot, character/character, setting, language style, and theme. Meanwhile, the function contained in the folklore of the MuaroPaitiNagari community is as entertainment, projection systems, equipment validating institutions and cultural institutions, and educational tools.